1985
DOI: 10.1177/070674378503000808
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Safety and Efficacy of Alprazolam and Desipramine in Moderately Severe Depression

Abstract: Fifty-four patients (34 outpatients, 20 inpatients) fulfilling Research Diagnostic Criteria for Definite Major Depressive Disorder were enrolled in a double-blind study comparing the antidepressant effects of alprazolam versus desipramine. The mean daily dose of alprazolam and desipramine at study termination was 3.78 mg and 208 mg respectively. As there were no significant demographic or clinical differences between outpatients and inpatients, both groups were combined in data analysis. Using the Hamilton Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Regarding response to treatment, 9 of these studies found an overall improvement, with no significant differences across medication classes [41-43, 45, 46, 49, 51, 52, 54], even in the setting of melancholia [54], in both outpatients and inpatients [49]. Results significantly favoring the use of TCA were found in 4 studies [44,47,48,50].…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 86%
See 2 more Smart Citations
“…Regarding response to treatment, 9 of these studies found an overall improvement, with no significant differences across medication classes [41-43, 45, 46, 49, 51, 52, 54], even in the setting of melancholia [54], in both outpatients and inpatients [49]. Results significantly favoring the use of TCA were found in 4 studies [44,47,48,50].…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 86%
“…Participants were assigned at random to the conditions in all studies, and all were double-blind trials. ITT analyses were performed in 8 reports [19,20,23,28,30,31,42,53], completers' data only were reported in 12 studies [25,27,29,37,39,41,44,45,47,49,50,54], and handling of attrition was not reported in 2 studies [46,48].…”
Section: Meta-analysis On the Efficacy Of Bzd In The Treatment Of Depmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also become apparent that seda tion during benzodiazepine use is responsible for increas ing outpatients' risk of injury and death in motor vehicle accidents. An early warning came from one clinical trial when 2 of 16 outpatients receiving alprazolam in a 3.5-mg average daily dose became involved in accidents before completing their scheduled 6-week treatment periods [2]. The latest evidence has come from a retrospective, casecontrol epidemiological survey.…”
Section: Introductionmentioning
confidence: 99%